SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JENIS BISNIS DENGAN METODE MULTIFACTOR EVALUATION PROCESS - Maulana, Reza; Awaru, Tenri (Jurnal INSYPRO (Information System and Processing), 2024)
ABSTRACT - Every business has its own ideal criteria regarding location, capital, and interests. The middle to lower-class economic status can also result from a lack of knowledge about how to start a business. Therefore, the aim of this thesis is to guide the community on how to initiate their own ventures in the location they inhabit. In this study, the Multifactor Evaluation Process (MFEP) method is employed to objectively evaluate critical aspects. For this thesis, the critical aspects needed are the community or consumer needs, required capital, business location, and business competitors. The desired outcome of this thesis is a website that displays the sequence of calculations, which will serve as a benchmark in determining the community's decision regarding the type of business to be established. Keywords: Decision Support System (DSS), Small and Medium Enterprises (SMEs), Multifactor Evaluation Process (MFEP).